The Madrid Qumran congress : proceedings of the International Congress on the Dead Sea Scrolls, Madrid, 18-21 March, 1991 - Trebolle Barrera, Julio C.; Vegas Montaner, Luis. (Studies on the Texts of the Desert of Judah, 1992)
The material presented in these two volumes may be divided into two main sections. The first section covers biblical texts and texts which fall between the categories biblical and non-biblical. It also includes articles on topics relating to the history of the Qumran community and to the study of the New Testament in the light of the Qumran discoveries. The second section covers non-biblical texts, such as the Temple Scroll. The two sections are synthesized in the article by Frank M. Cross, in which he reviews the advances made and the challenges for the future in the field of Qumran studies. Several topics recur constantly in many of the articles, such as the origins of the history of the Qumran community, the problem of the distinction between what is biblical and non-biblical in the Qumran manuscripts, and the question of the authority of the texts in the Qumran community.